Efforts To Overcome Physical Violence Against Children In Households In Denpasar City - Kadek Laksmi Wulandari A.; AAA. Ngurah Tini Rusmini Gorda (Universitas Pendidikan Nasional, 2024)
Violence is an act committed by an individual against another individual that causes physical or mental disorders. One of them is violence that occurs in children, namely physical violence. The purpose of this study is to determine how efforts to overcome criminal acts of physical violence against children in households in the city of Denpasar. The type of method used in this study is the empirical legal method which is a type of sociological legal research and can be called field research by examining primary data. The results of this study are efforts to overcome criminal acts of physical violence against children in households in the city of Denpasar by making two efforts, namely preventive legal protection efforts and repressive legal protection efforts. Preventive efforts are made by conducting socialization about children's rights, socialization of parental emotional management, and implementing anti-violence campaigns, and repressive efforts are made by conducting socialization of child complaint and protection services, and stop violence campaigns. The conclusion of this study is that economic factors, emotional factors and efforts to overcome are carried out by conducting socialization.The socialization conducted by the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) of Denpasar City is a strategic effort to prevent physical violence against children in the household. This activity not only increases public awareness of the negative impacts of violence, but also builds a shared commitment to protect children as the next generation of the nation. Through an approach involving various parties, such as the community and schools, it is hoped that the number of cases of violence against children can decrease significantly in Denpasar City. The socialization conducted by the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) of Denpasar City is a strategic step in preventive and repressive efforts to overcome criminal acts of physical violence against children in the household.